Kebijakan Formulasi Hukum Pidana Terkait Wajib Menyalakan Lampu Utama pada Siang Hari Dalam Pasal 107 Ayat (2) Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Reza Iswanto (Universitas Batanghari Jambi, 2019)
Current traffic accidents continue to occur on the highway so it does not rule out the possibility of casualties. For this reason, Law Number 22 Year 2009 concerning Traffic and Road Transportation has been issued as amended by Law Number 14 of 1992 concerning Road Traffic and Transportation. In Law Number 22 of 2009 concerning Road Traffic and Transportation there are more specific arrangements regarding requiring motorbike riders to turn on their main motorbike lights during the day, namely Article 107 Paragraph (2) of Law Number 22 2009 concerning Road Traffic and Transportation. The background of the policy on the formulation of criminal law Article 107 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation is that Law Number 14 of 1992 concerning Road Traffic and Transportation is no longer compatible with conditions, strategic environmental changes and the need to carry out Road Traffic and Transportation at this time and to realize security and reduce the number of accidents that always increase every year. However, the implication of Article 107 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation is the greater loss obtained than the benefits generated. Therefore, the impending formulation of criminal law policy related to Article 107 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation is the abolition of Article 107 Paragraph (2) Law Number 22 Year 2009 concerning Traffic and Road Transportation. To get the results of this study, the normative legal approach is used by prioritizing library materials or secondary data which is carried out by analyzing Article 107 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation and then associated with expert opinion